Faktor-Faktor Yang Mempengaruhi Kepatuhan Minum Obat Anti Tuberkulosis di UPTD Rumah Sakit Khusus Paru Provinsi Sumatera Utara - Laowo, Oktorisman; Dachi, Rahmat Alyakin; Tarigan, Frida Lina; Manurung , Kesaktian; Sinaga, Janno (Journal of Pharmaceutical and Sciences, 2025)
Tuberculosis (TB) is a preventable and usually curable disease. Yet, it remains one of the leading causes of death in the world, especially in high TB-burden countries such as Indonesia. In 2021, there was a significant increase in TB incidence and mortality in Indonesia, especially in North Sumatra province, which reported many TB cases, including drug-resistant TB (MDR-TB). Patient non-adherence to treatment is a significant factor exacerbating this situation, leading to increased drug resistance and broader transmission. Strategic efforts and treatment adherence are needed to address the TB epidemic, in line with the global TB elimination target by 2030. This study aims to determine the factors influencing adherence to anti-tuberculosis drugs at the UPTD Pulmonology Hospital of North Sumatra Province. The study was a quantitative study with a cross-sectional research design. The sample in this study was 37 people, with sampling using accidental sampling, and the data were analysed univariate, bivariate with the Chi-Square test at α = 5% level, and multivariate with multiple logistic regression test. The results of this study showed that there was an influence of knowledge on adherence to taking anti-tuberculosis drugs (p-value = 0.038), employment (p-value = 0.018), access to health services (p-value = 0.003), and family support (p-value = 0.006). There was no influence of medication's side effects on adherence to anti-tuberculosis drugs (p-value = 1) at the UPTD Pulmonology Hospital of North Sumatra Province. The dominant factor in this study was family support, which tended to be more compliant with taking anti-tuberculosis drugs by 19 times compared to respondents who received less family support. This study recommends that the UPTD Pulmonology Hospital of North Sumatra Province increase family involvement and education in supporting the treatment of tuberculosis patients, including family assistance programs, counselling on the importance of family support, and providing information related to drug side effects so that families can provide proper motivation and understanding to patients.